ExoMol line lists – XLIV. Infrared and ultraviolet line list for silicon monoxide (28Si16O). Issue 1 (12th November 2021) - Yurchenko, Sergei N; Tennyson, Jonathan; Syme, Anna-Maree; Adam, Ahmad Y; Clark, Victoria H J; Cooper, Bridgette; Dobney, C Pria; Donnelly, Shaun T E; Gorman, Maire N; Lynas-Gray, Anthony E; Meltzer, Thomas; Owens, Alec; et al.
ABSTRACT: A new silicon monoxide ( 28 Si 16 O) line list covering infrared, visible, and ultraviolet regions called SiOUVenIR is presented. This line list extends the infrared EBJT ExoMol line list by including vibronic transitions to the A ^1Π and E ^1Σ ^+ electronic states. Strong perturbations to the A ^1Π band system are accurately modelled through the treatment of six dark electronic states: C ^1Σ ^-, D ^1Δ, a ^3Σ ^+, b ^3Π, e ^3Σ ^-, and d ^3Δ . Along with the X ^1Σ ^+ ground state, these nine electronic states were used to build a comprehensive spectroscopic model of SiO using a combination of empirical and ab initio curves, including the potential energy (PE), spin–orbit, electronic angular momentum, and (transition) dipole moment curves. The ab initio PE and coupling curves, computed at the multireference configuration interaction level of theory, were refined by fitting their analytical representations to 2617 experimentally derived SiO energy levels determined from 97 vibronic bands belonging to the X – X, E – X, and A – X electronic systems through the MARVEL (Measured Active Rotational–Vibrational Energy Levels) procedure. 112 observed forbidden transitions from the C – X, D – X, e – X, and d – X bands were assigned using our predictions, and these could be fed back into the MARVEL procedure. The SiOUVenIR line list was computed using published ab initio transition dipole moments for the E – X and A – X bands; the line list is suitable for temperatures up to 10 000 K and for wavelengths longer than 140 nm. SiOUVenIR is available from www.exomol.com and the CDS data base.